1995
DOI: 10.1159/000236968
|View full text |Cite
|
Sign up to set email alerts
|

Prevention by Monovalent Haptens of IgE-Dependent Leucocyte Histamine Release to Muscle Relaxants

Abstract: The cross-reactivity between muscle relaxants (MRs) is a risk for inducing anaphylaxis in sensitized patients. The preventive use of monovalent haptens (MHs) was studied in 21 cases. Inhibition of the skin reactivity by mixing MRs and MHs was observed, as was the inhibition of leucocyte histamine release to MRs, up to 3 h after infusion of MHs. These results argue for the use of such a protocol, if surgery requires the use of a MR in patients at risk for anaphylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As a result, the concentrations obtained were too low to be effective [55,56]. Recently, Moneret-Vautrin et al [57] demonstrated inhibition of skin mast-cell reactivity to muscle relaxants by mixing them with the monovalent haptens cytidylcholine and ethamsylate. Furthermore, they obtained an inhibition of leukocyte histamine release for up to 3 hours following the infusion of these monovalent haptens in patients allergic to muscle relaxants.…”
Section: Preventionmentioning
confidence: 99%
“…As a result, the concentrations obtained were too low to be effective [55,56]. Recently, Moneret-Vautrin et al [57] demonstrated inhibition of skin mast-cell reactivity to muscle relaxants by mixing them with the monovalent haptens cytidylcholine and ethamsylate. Furthermore, they obtained an inhibition of leukocyte histamine release for up to 3 hours following the infusion of these monovalent haptens in patients allergic to muscle relaxants.…”
Section: Preventionmentioning
confidence: 99%
“…47 Some authors favor intradermal tests on the back because the skin is less exposed to and modified by physical agents. 13 However, in a report regarding a prick test, the skin reactivity was less notable on the forearm than on the back for both histamine and allergen. 48 At that time, such data were lacking for intradermal tests and NMBAs.…”
Section: Discussionmentioning
confidence: 95%
“…36 This is probably why the performance of skin tests for the diagnosis of sensitization against NMBAs has been considered as excellent by most of the authors. 1,2,5,7,9,[11][12][13]15,17,18,21,37,38 Indeed, the diagnostic value of an intradermal test in patients having presented with a suspected IgE-mediated immediate hypersensitivity reaction during anesthesia was established many years ago using Prausnitz-Kustner testing in human subjects. 11,37,39 Its excellent reproducibility 10 as well as persistence of positivity with time 10,40,41 has also been confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation